Estudo da utilização de conceitos biomiméticos no perfil hidrodinâmico NACA 4412 - Bottlender, Pedro Henrique Melo (2023)
Brazil is one of the great countries that generate electricity through hydraulic energy. In a hydroelectric power plant, the hydraulic turbines are the only ones responsible for transforming hydraulic energy into mechanical energy, to be later transformed into electrical energy. The rotor is one of the most important components found in turbines, and blades of some hydraulic turbines, such as Kaplan and Francis turbines, are formed by aerodynamic profiles, which must be validated and tested before being applied in hydraulic turbine designs. Thus, it can be stated that airfoils are surfaces that cause pressure differences, resulting in velocity differences between the upper surface and lower surface, generating aerodynamic effects. Thinking about innovation in the area, biomimetics can be a good alternative, which consists in being inspired by biological organisms to carry out projects in different branches of knowledge, or also, to apply basic principles of nature in projects and studies. The humpback whale can serve as inspiration, because it is a mammal that, when preying, has the ability to perform spinning maneuvers, an ability found because they have protuberances on the entire leading edge of their large fins, improving the flow control and flexibility of their maneuvers. Thus, this work aims to identify the main gains of hydrodynamic profiles NACA 4412 modified with the use of tubercles from flow analysis. To perform the study four hydrofoils were modeled, M1, M2, M3 and M4, three of these with sinusoidal characteristics at the leading edge, varying the wavelength and amplitude of the protrusions. The study was performed in ANSYS Fluent software, the computational domain defined based on bibliographic references to meet the needs of the simulations, the mesh was verified from tests of mesh independence and the model validated through the analysis of the pressure and lift coefficients, and all simulations using water as the working fluid. To perform the computational analyses, different angles of attack were considered, a range of 0 to 25 degrees. When compared to the standard profile, the NACA 4412 hydrofoils modified with tubers lost lift earlier, starting at 6 degrees of pitch. After 5 degrees, the drag coefficients become larger for the modified profiles. The drag polar plot shows that for low drag coefficients the tubercles hydrofoil showed higher support, but the modified hydrofoils showed higher support for higher drag coefficients. For 20 and 25 degrees, it was possible to verify a delay at the point of displacement of the boundary layer, especially for the M4 configuration. For alpha=25º it was identified irregular flow and with recirculations in 2/3 along the modified profiles, as for the hydrofoil without modification this characteristic of the flow reaches regions even closer to the leading edge, but has places where the recirculations are smaller. Despite the difficulties presented, new and interesting results emerged. It was possible to show that the insertion of tubercles on the leading edge of the profiles presented result in interesting characteristics in the analysis of the lift and drag coefficients, as well as in the velocity and boundary layer fields.